Oral-Gut Microbiome Axis in the Pathogenesis of Cancer Treatment-Induced Oral Mucositis - Al-Qadami, Ghanyah; Van Sebille, Ysabella; Bowen, Joanne; Wardill, Hannah (Frontiers in Oral Health, 2022)
Oral mucositis (OM) is one of the most common and debilitating oral complications of cancer treatments including chemotherapy, radiotherapy, and hematopoietic stem cell transplantation. It is associated with severe pain and difficulties in chewing, swallowing, and speech. This leads to impairment of basic oral functions and could result in unplanned treatment interruption or modification. As such, OM negatively impacts both patients' quality of life as well as tumor prognostic outcomes. Understanding pathways underlying OM pathogenesis help identify new targets for intervention or prevention. The pathophysiology of OM has been widely studied over past decades with several pathways related to oxidative stress, inflammation, and molecular and cellular signaling being implicated. In this mini-review, we will discuss the emerging role of the oral-gut microbiome axis in the development of OM. Particularly, we will elaborate on how the alterations in the oral and gut microbiota as well as intestinal dysfunction caused by cancer treatments could contribute to the pathogenesis of OM. Further, we will briefly discuss the potential methods for targeting the oral-gut microbiome axis to improve OM outcomes.